An appraisal of museum education programmes for primary school pupils in post colonial Zimbabwe - Chitima, Simbarashe Shadreck (Midlands State University, 2021)
This study investigates the success of museum educational programmes in Zimbabwe in facilitating effective learning of curriculum related content amongst primary school pupils. My thesis is that while museums in Zimbabwe have a long tradition of providing education programming, the behaviourist education framework grounding museum education provides few opportunities for primary school pupils to effectively learn. This study is grounded on Sociocultural learning frameworks. Through the use of qualitative and quantitative research approaches, the study gathered that museums are contributing to national education goals by impacting on the social and environmental studies curriculum. The major barriers to pupil‘s learning are categorised as structural, physical and intellectual. The educational philosophy and some of the instructional media used to impart knowledge to pupils in museums still carry the remnants of the colonial education service. Museums in Zimbabwe base their educational programming on the behaviourist educational framework and this is restrictive to effective learning in informal settings. Behaviourism in museums in Zimbabwe has created a situation where primary school pupils become epistemological slaves only to be deposited with information. The study concludes that they are few opportunities in museums for primary school pupils to effectively learn curriculum content. There is need to decolonise museum education service in Zimbabwe that touches on the educational philosophy, museum exhibition design, narratives, language in use and interpretations as well as methods of content delivery.